2023
DOI: 10.1177/15353702221142619
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in muscle SIRT1 and SIRT3 and exercise + weight loss effects on muscle sirtuins

Abstract: The sirtuins, SIRT1 and SIRT3, are involved in the control of cellular processes to maintain metabolic homeostasis. The purpose of this study was to determine the effects of a 6-month aerobic training + weight loss program and hyperinsulinemia on SIRT1 and SIRT3 expression in skeletal muscle and to compare their expression between men and women. Thirty-five adult men ( n = 18) and postmenopausal women ( n = 17), (X ± SEM, age: 61 ± 1 years, BMI: 31.3 ± 0.7 kg/m2) completed 6 months 3×/week of aerobic exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…It is important to note that we did not find significant differences of SIRT1 expression or FMD after energy restriction (Table 1), but only correlations (baseline SIRT1 expression and ∆FMD) which may not necessarily reflect causality. Women did not have this association because, perhaps, of the fact that they presented, in the basal state, higher SIRT1 [50,51] and FMD [54] than men due to estrogens, and the interventions of the present study were not sufficient to optimize these parameters in this group.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It is important to note that we did not find significant differences of SIRT1 expression or FMD after energy restriction (Table 1), but only correlations (baseline SIRT1 expression and ∆FMD) which may not necessarily reflect causality. Women did not have this association because, perhaps, of the fact that they presented, in the basal state, higher SIRT1 [50,51] and FMD [54] than men due to estrogens, and the interventions of the present study were not sufficient to optimize these parameters in this group.…”
Section: Discussioncontrasting
confidence: 55%
“…Laboratory studies showed that, in female rats, estrogen activated the SIRT1/AMPK signaling pathway, increasing protection against cerebral ischemic stress [46] and angiotensin (Ang) II-induced cardiomyocyte hypertrophy [47], which could explain the mechanisms behind the epidemiological differences of cardiovascular diseases between men and women [48,49]. Previous studies showed differences between men and women regarding sirtuin levels in heart and skeletal muscle tissues [50,51], corroborating the hypothesis that women have an increased baseline sirtuin content, probably due to higher levels of circulating estrogens. Therefore, our results support that interventions that increase SIRT1 may be more effective in men with lower baseline SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we extend findings in the literature that there are baseline sex differences in skeletal muscle metabolism [7][8][9][10], specifically the change in GS fractional and independent activity and AKT protein expression with insulin stimulation. Also, basal AMPK, GSK-3β, ERK1/2, and p38 are each lower in older men than in older women.…”
Section: Discussionsupporting
confidence: 87%
“…We have also found that middle‐aged and older women have higher adipose tissue expression of adiponectin, an adipokine that regulates lipid and glucose metabolism, and higher adipose and skeletal muscle tissue expression of liver receptor homolog‐1 (LRH‐1), a nuclear receptor that regulates lipid metabolism, than similar aged men [8]. Furthermore, we have reported higher skeletal muscle expression of sirtuins SIRT1 and SIRT3 , genes involved in metabolic homeostasis [9], and lower myostatin expression in women than men [10]. Taken together, these results suggest that differences between men and women in both adipose tissue and skeletal muscle contribute to the overall observed sex differences regulating metabolism that occur with age.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast to androgen levels in males, androgen levels in females are naturally in the castration range (Matsumoto & Bremner, 2004). Despite naturally low androgen levels, SIRT1 levels in the limb muscle of females are reported to be higher than in the muscle of testicular intact males (Ryan & Li, 2023). Therefore, it was not surprising that neither total lean mass, nor limb muscle mass was enhanced by increasing SIRT1 protein in the muscle of females, probably because the females already had sufficient SIRT1 levels to maintain limb muscle mass (i.e.…”
Section: Discussionmentioning
confidence: 99%